2022
DOI: 10.21203/rs.3.rs-1179114/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First report of rapid, non-invasive, and reagent-free detection of malaria through the skin of patients with a beam of infrared light

Abstract: We describe the first application of the Near-infrared spectroscopy (NIRS) technique to detect Plasmodium falciparum and P. vivax malaria parasites through the skin of malaria positive and negative human subjects. NIRS is a rapid, non-invasive and reagent free technique which involves rapid interaction of a beam of light with a biological sample to produce diagnostic signatures in seconds. We used a handheld, miniaturized spectrometer to shine NIRS light on the ear, arm and finger of P. falciparum (n=7) and P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…If further assessed these arboviruses and P. falciparium could be developed into biomarkers of these pathogens in human samples. NIRS is an easy to use, rapid, potable, and reagent free technique [67, 7577]. Once machine learning techniques are developed, the feasibility for on-site largescale diagnosis of patients is feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If further assessed these arboviruses and P. falciparium could be developed into biomarkers of these pathogens in human samples. NIRS is an easy to use, rapid, potable, and reagent free technique [67, 7577]. Once machine learning techniques are developed, the feasibility for on-site largescale diagnosis of patients is feasible.…”
Section: Discussionmentioning
confidence: 99%
“…If further assessed these arboviruses and P. falciparium could be developed into biomarkers of these pathogens in human samples. NIRS is an easy to use, rapid, potable, and reagent free technique [67,[75][76][77].…”
Section: Discussionmentioning
confidence: 99%
“…The study in Brazil showed 92% accuracy for the arm and 93% predictive accuracy for differentiating between P. falciparum and P. vivax . The bands observed in the spectra enable the identification of positive and negative malaria cases and are mainly due to hemozoin [ 208 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%